Psikoedukasi Dzikr Menurunkan Kadar Kortisol dan Meningkatkan Kadar IGG pada Ibu Primipara - Sri Wahyuni; Anies Anies; Ariawan Soejoenoes; Suhartono Taat Putra (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2018)
Background: Unstable emotions that are common during the perinatal period affect hormonal regulation and affect immunity. Research of psychoeducation dhikr be important was done to reduce perceived stress so that cortisol levels can be controlled hence IgG increases.Purposes: to prove additional psychoeducation of dhikr in routine midwifery care more influential on decreasing cortisol and increasing IgG among primiparous women.Methods: This study was an experimental study. A number of 24 participants as intervention group and a number of 23 participants as control group. Cortisol and IgG levels measured using ELIZA kits in the third trimester of pregnancy, the three days and tenth days after birth. Statistical test using General Linear Model and independent t test to compare Δ score.Results: The result showed mean difference between groups on the end of interventions, cortisol 18.95, CI 95% (-13.42 – 51.33) and p value is 0.245. The difference of the IgG between groups 482.72, CI 95% (55,51 - 909,93) and p value is 0.028.Conclusions: Additional psychoeducation of dhikr in routine midwifery care has more decrease Cortisol and increase IgG levels in primiparous women. Keywords: Cortisol, Psychoeducation Dzikr, IgG, Primiparous